THE EFFECT OF COMBINED NITROGEN SOURCE ON THE GROWTH AND YIELDS OF PAKCOY IN PEAT SOIL - Cahyadi, Andri Septian (Fakultas Pertanian Universitas Tanjungpura, 2021)
ABSTRACTThis study aims to find the best combination of nitrogen sources in the form of ammonium and nitrate for growth and yield of pakcoy on peat soils. This research was conducted at the green house of the Faculty of Forestry, Tanjungpura University, Pontianak City with an altitude of 5 meters above sea level. The time of this study lasted for ± 3 months. The research used a completely randomized design (CRD) consisting of one treatment factor, namely a combination of nitrogen sources with 5 (five) treatment levels with 5 (five) replications, and each treatment consisting of 5 (five) sample plants, so that there were 125 plants. The treatments analyzed were: n1 = 100% NH4+ + 0% NO3- ; n2= 75% NH4+ + 25% NO3- ; n3 = 50% NH4+ + 50% NO3- ; n4 = 25% NH4+ + 75% NO3- ; n5 = 0% NH4+ + 100% NO3-. The variables observed were the number of leaves (strands), leaf chlorophyll content, leaf area, root volume and plant dry weight. The effect of giving a combination of nitrogen fertilizers had a significant effect on root volume, number of leaves, dry weight, and area and, but not significantly, on leaf chlorophyll content variables. The combination of 50% NH4+ + 50% NO3- provides the best growth and yield of pakcoy on peat soils. Keywords: combination of nitrogen sources, pakcoy, peat